2020
DOI: 10.1111/cge.13774
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exome sequencing in fetuses with congenital heart defects

Abstract: The genetic diagnosis of congenital heart defects (CHDs) is challenging because of genetic and phenotypic heterogeneity. The aim of our study was to evaluate the clinical value of whole exome sequencing (WES) in the prenatal diagnosis of CHDs in a large cohort. Trio‐based WES was performed in 260 fetuses with CHDs negative for karyotype and chromosome microarray analysis results. WES produced a diagnostic yield of 10% (26/260) in the entire cohort. Relative high diagnostic rate was observed in cases with cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 26 publications
4
34
2
Order By: Relevance
“…Ultrasound scans showed a range of abnormalities including increased nuchal translucency, pleural effusion, cardiac anomaly, renal anomalies, intrauterine growth restriction, polyhydramnios, oligohydramnios and single umbilical artery. Similar antenatal presentations were also noted in the recent large case series and published case reports 8–40 . More than half of the cases were diagnosed after birth by clinical assessment and molecular testing.…”
Section: Discussionsupporting
confidence: 78%
“…Ultrasound scans showed a range of abnormalities including increased nuchal translucency, pleural effusion, cardiac anomaly, renal anomalies, intrauterine growth restriction, polyhydramnios, oligohydramnios and single umbilical artery. Similar antenatal presentations were also noted in the recent large case series and published case reports 8–40 . More than half of the cases were diagnosed after birth by clinical assessment and molecular testing.…”
Section: Discussionsupporting
confidence: 78%
“…Overall, the yield of the CMA test in our study was consistent with previously published data. However, the detection rate of our pathogenic sequence variants is higher than that reported in the literature [23][24][25] . In conclusion, we suggest CMA as a rst-tier test in fetuses with CHD, and that WES can be offered sequentially if CMA results are negative.…”
Section: Discussioncontrasting
confidence: 70%
“…Similar results have been obtained in previously published data. Wang et al reported that among 602 cases of CHD detected by CMA, the most common chromosomal abnormalities were observed in fetuses with AVSD (73.7%) 23 . Although the subgroup size of our cohort was small, we got very similar results with Wang's study.…”
Section: Discussionmentioning
confidence: 99%
“…A random-effects model was used to estimate the yield for isolated and multisystem CHD and the yield overall using RevMan version 5.3.4 (Review Manager, The Cochrane Collaboration, Copenhagen, Denmark) 22 . This model pooled our findings with those of 18 studies of 1557 fetuses, based on the analysis of Mone et al 5 and including two more recent studies 4,17 . It allowed for treatment effects to vary across studies and used a simple non-iterative method to estimate the interstudy treatment effect variance.…”
Section: Statistical Analysesmentioning
confidence: 86%
“…Pathogenic CNVs have been detected in 7-36% of fetuses with isolated CHD or CHD associated with other structural anomalies but normal karyotype 6,8 . Next-generation sequencing, especially exome sequencing (ES), enables analysis of single nucleotide variations (SNV) and insertions and deletions (indels) of gene-coding regions, and has facilitated in CHD patients discovery of novel causative genes 4,[14][15][16][17] which are indefinable through traditional genomic methods. However, previous fetal studies have focused on chromosomal abnormalities and sequence variants separately.…”
Section: Introductionmentioning
confidence: 99%